Evaluation of an Intervention to Support Patient‐Rheumatologist Conversations About Escalating Treatment in Patients with Rheumatoid Arthritis: A Proof‐of‐Principle Study. Issue 4 (27th December 2021) - Danila, Maria I.; Chen, Lang; Ruderman, Eric M.; Owensby, Justin K.; O'Beirne, Ronan; Melnick, Joshua A.; Harrold, Leslie R.; Curtis, David; Nowell, W. Benjamin; Curtis, Jeffrey R.
Abstract : Objective: This study's objective was to test whether an online video intervention discussing appropriate treatment escalation improves willingness to change treatment in people living with rheumatoid arthritis (RA). Methods: We conducted a controlled, randomized trial among patients with RA enrolled in ArthritisPower, a United States patient registry. We recruited participants by email and surveyed their assessment of disease activity (patient global), satisfaction with disease control (patient acceptable symptom state), attitudes about RA medications, decisional conflict (decisional conflict scale), and willingness to modify RA treatment (choice predisposition scale, higher scores are better) if or when recommended by their rheumatologist. Intervention groups watched educational videos relevant to a treat‐to‐target (T2T) strategy, whereas control groups viewed vaccination‐related videos as an "attention control." We compared the between‐group difference in patients' willingness to modify RA treatment (primary outcome) and difference in decisional conflict about changing RA treatment (secondary outcome) after watching the videos using t tests. Results: Participants with self‐reported RA (n = 208) were 90% White and 90% women, with a mean (standard deviation) age of 50 (11) years, and 52% reported familiarity with the RA T2T strategy. We found a significant improvement in between‐group difference in willingness to change RA treatment among intervention versus control participants (0.49 [95% confidence interval 0.09‐0.88], P  = 0.02). The effect size (Glass's delta) for the intervention was 0.48. Decisional conflict about treatment change decreased, but the between‐group difference was not significant. Conclusion: This novel educational patient‐directed intervention discussing appropriate treatment escalation was associated with improved willingness to change RA treatment if or when recommended by a rheumatologist. Further studies should evaluate whether this change in patients' predisposition translates into actual treatment escalation.